Capacity of Japanese Asobara species (Hymenoptera; Braconidae) to parasitize a fruit pest Drosophila suzukii (Diptera; Drosophilidae). (10th June 2014) - Nomano, F. Y.; Mitsui, H.; Kimura, M. T.
Abstract Drosophila suzukii is a pest of soft fruit such as cherry, strawberry or blueberry and recently colonized North America and Europe from Asia. In this study, we assessed the utility of Japanese Asobara species as agents for the biological control of this pest species by examining their host use in nature and their capacity to parasitize this pest species. From Japan, eight Asobara species including putative three undescribed species were found; Asobara japonica was recorded from all over Japan, Asobara tabida from high altitude areas in central and northern Japan, Asobara rossica and Asobara rufescens from central to northern Japan, three undescribed species from central to western or southern Japan and Asobara pleuralis from a subtropical island of Japan. Among them, an undescribed species Asobara sp. TK1 may be useful as an agent for the biological control because it was recorded only from D. suzukii. All of the remaining seven species were generalists mainly using drosophilid species associated with fermenting fruits, and four of them had no or very low abilities to parasitize D. suzukii, indicating that these seven species are not or less appropriate as agents for biological control.